Worth any price ebook - Kleypas, Lisa (Bow Street Runners, 2009)
Nick Gentry, the most seductive and dangerous man in England, has been sent to find Charlotte Howard, a runaway bride who has disappeared without a trace. But when he finds her, Nick is stunned by the intensity of his attraction to the elusive young woman whose adventurous spirit matches his own. Determined to escape a forced marriage to a man who will destroy her, Charlotte agrees to an audacious bargain . . . she will become Nick Gentry's bride. But soon she discovers that Nick has secrets of his own, and it will take all her wits and stubborn will to tame his tormented soul. In the desperate quest to protect Charlotte from the diabolical aristocrat who threatens her, one thing becomes clear: To save the woman he loves, Nick will take any risk . . . and pay any price.